Product Cost Calculation in Model-Based Systems Engineering - Georg Hartmann; Thilo Zerwas; Lisa Domröse; Kathrin Boelsen; Christian Hilger; Simon Schnürer (Systems)
In product development, costs play a major role in making design decisions. As such, it is desirable to have this information as early as possible in the product development process (PDP). The development of systems changes in the direction of Model-Based Systems Engineering (MBSE) with a system model containing all information. The product costs thus need to be considered in MBSE approaches and system models. In the early stages, cost calculation models are rough estimates and will become more refined over the course of the PDP. The flow of information between the product information and cost calculation models takes a long time, and multiple calculations need to be updated before the product cost can be calculated. In this contribution, we show how cost types like the manufacturing cost or purchase cost can be seamlessly integrated into a hierarchical product structure, and cost calculation models can be linked. We present how cost calculation models with different granularity can be changed over the course of the PDP and how the product cost calculation is affected when a specific factor of the product changes. In this contribution, the case of the electrohydraulic actuator (EHA) developed in the project “Dezentrale Hydraulik II” is used.